Low pH conditions impair module capacity to regenerate in a calcified colonial invertebrate, the bryozoan Cryptosula pallasiana. (April 2017) - Lombardi, Chiara; Taylor, Paul D.; Cocito, Silvia; Bertolini, Camilla; Calosi, Piero
Abstract: Many aquatic animals grow into colonies of repeated, genetically identical, modules (zooids). Zooid interconnections enable colonies to behave as integrated functional units, while plastic responses to environmental changes may affect individual zooids. Plasticity includes the variable partitioning of resources to sexual reproduction, colony growth and maintenance. Maintenance often involves regeneration, which is also a routine part of the life history in some organisms, such as bryozoans. Here we investigate changes in regenerative capacity in the encrusting bryozoan Cryptosula pallasiana when cultured at different seawater p CO2 levels. The proportion of active zooids showing polypide regeneration was highest at current oceanic pH (8.1), but decreased progressively as pH declined below that value, reaching a six-fold reduction at pH 7.0. The zone of budding of new zooids at the colony periphery declined in size below pH 7.7. Under elevated p CO2 conditions, already experienced sporadically in coastal areas, skeletal corrosion was accompanied by the proportional reallocation of resources from polypide regeneration in old zooids to the budding of new zooids at the edge of the colony. Thus, future ocean acidification can affect colonial organisms by changing how they allocate resources, with potentially profound impacts on life-history patterns and ecological interactions. Highlights: First information about changes in regenerative capacity in a colonial marine invertebrate under Future Oceans (2100, 2300). Decrease of regeneration of active modular units with declining pH, reaching a six-fold reduction pH expected at 2300. Skeletal corrosion is accompanied by the proportional reallocation of resources from regeneration to new budding. Altered regenerative capacity, induced by Ocean Acidification, impacts on life history patterns and ecosystem dynamics.